The Importance of Sensory Education in Mental Development of Preschool Children - Nigmatova Mavjuda Zuvaydulloyevna (International Journal on Integrated Education, 2022)
This article describes the specific features of the process of sensory education of children of preschool age. It is stated that games play an important role in development of this process.